2015
DOI: 10.1002/mc.22321
|View full text |Cite
|
Sign up to set email alerts
|

LW-213 induces G2/M cell cycle arrest through AKT/GSK3β/β-catenin signaling pathway in human breast cancer cells

Abstract: LW-213 is a derivative of Wogonin and the anticancer activities of Wogonin have been reported. To study whether LW-213 inhibits cancer cells and explore a possible mechanism, we investigate the compound in several cancer cell lines. We found LW-213 arrests G2/M cycle in breast cancer cells by suppression of Akt/Gsk3β/β-catenin signaling pathway. In compound treated cells, cell cycle-related proteins cyclin A, cyclin B1, p-CDK1, p-Cdc25C, and p-Chk2 (Thr68) were upregulated, and β-catenin nuclear translocation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 43 publications
2
24
0
Order By: Relevance
“…It has been demonstrated that there exists crosstalk between the Wnt/β-catenin signalling pathway and several other signalling pathways in breast cancer, including those involving MAPKs and Akt, suggesting inhibition of β-catenin may depend on MAPKs and/or Akt signalling [25, 26]. Indeed, PLCD1 induces cell cycle arrest by inhibiting Akt signalling in ESCC [6], and suppresses EMT through ERK signalling in KRAS-mutated colorectal cancers [7].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that there exists crosstalk between the Wnt/β-catenin signalling pathway and several other signalling pathways in breast cancer, including those involving MAPKs and Akt, suggesting inhibition of β-catenin may depend on MAPKs and/or Akt signalling [25, 26]. Indeed, PLCD1 induces cell cycle arrest by inhibiting Akt signalling in ESCC [6], and suppresses EMT through ERK signalling in KRAS-mutated colorectal cancers [7].…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of Wnt, cytoplasmic β-catenin is phosphorylated on several serine and threonine residues by a destruction complex containing GSK3β, casein kinase1 (CK1), axin and adenomatous polyposis coli (APC), which leads to ubiquitin-proteasome-mediated degradation of β-catenin [27, 55]. Lithium chloride (LiCl) is known to activate canonical Wnt signaling by inhibiting GSK3β and consequently stabilizing free cytosolic β-catenin [56, 57]. Coincidently, in our study we found that depletion of polyamine induced by SSAT over-expression decreased p-GSK3β expression and inhibited β-catenin nuclear translocation in hepatocellular and colorectal carcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…GSK-3β also functions as a tumor suppressor, because GSK3β can suppress the Wnt/β-catenin pathway by phosphorylating β-catenin [40]. Moreover, β-catenin transactivation has been associated with cyclin D1 overexpression in breast cancer [46].…”
Section: Discussionmentioning
confidence: 99%